Diagnóstico da tuberculose em pessoas idosas: barreiras de acesso - Oliveira, Annelissa Andrade Virgínio de (2011)
The delay in the diagnosis of tuberculosis (TB) has been highlighted as a problem to control this disease and reflects challenges related to health care system and involves aspects related to patients and health services. Sticking to shift the incidence of TB in the age group of the elderly, the greater difficulty of diagnosis in this portion of the population and the need to develop research aimed to identify the aspects that contribute to delayed diagnosis of TB, this study aims to analyze the barriers to access to TB diagnosis in older people contributing to the delayed diagnosis of the disease in the city of Joao Pessoa, Paraiba. It is a qualitative evaluative study involving seven employees. Inclusion criteria were: being in treatment, being more than 60 years, and reside in the city of Joao Pessoa. The empirical material was produced by means of taped interviews from December 2010 to February 2011. The transcribed interviews were organized using Atlas.ti software version 6.2 and in the process of empirical analysis used discourse analysis of the French headquarters. According to the speeches of the elders interviewed, it was possible to identify barriers were identified related to the sick and those related to health services. Among the barriers related to patients were identified: lack of knowledge about TB, the perceived seriousness of the disease and the use of household medications and self-medication, the search for direct health care in secondary and tertiary levels; seeking behavior by late health service, the nonspecific clinical presentation of TB in the elderly, the distance of the services demanded and transportation expenses and examinations, difficulties in collecting sputum for examination and the stigma associated with TB. Already as barriers related to health services, stood out: the opening hours of the family health units, transfer of responsibility, improper assessment of cases with respiratory symptoms in the community, not to carry out home visits or their achievement without control communicating, the delay of the health service-related delay in the suspicion of the disease and the need to make several visits to the health service to obtain the diagnosis. Faced with the evident barriers identified the need for a reorganization of health services in the country with the organization of supply as a function of the needs of the services, the delivery of training in TB health professionals, strengthening actions to narrow the relationships between professionals and users - encouraging the formation of bonding - the formation of groups and health education aiming at the strengthening of educational and health promotion. Despite of the National Primary Care recommend that the diagnosis of TB should be performed on the first level of health care for the elderly in the study, the diagnosis of TB occurred in other levels of care. Therefore, it is expected that the findings of this study contribute to the strengthening of primary care as gateway to the health system and more than that, contribute to the diagnosis of TB be given early.